Novel Budesonide Suppository and Standard Budesonide Rectal Foam Induce High Rates of Clinical Remission and Mucosal Healing in Active Ulcerative Proctitis: a Randomised, Controlled, Non-inferiority Trial. (16th June 2022) - Kruis, Wolfgang; Siegmund, Britta; Lesniakowski, Konrad; Simanenkov, Vladimir; Khimion, Ludmila; Sobon, Marcin; Delmans, Glebs; Maksyashina, Svetlana V; Sablin, Oleg A; Pokrotnieks, Juris; Mostovoy, Yuriy; Datsenko, Olena; et al.
Abstract: Background and Aims: Proctitis is the least extensive type of ulcerative colitis, for which rectal therapy is rarely studied and is underused. This study evaluated the efficacy, safety, and patient's preference of a novel formulation of budesonide suppository 4 mg, compared with a commercially available budesonide rectal foam 2 mg, for the treatment of mild to moderate ulcerative proctitis. Methods: This was a randomised, double-blind, double-dummy, active-controlled trial. Patients were randomly assigned in a 1:1 ratio to receive either budesonide 4 mg suppository or budesonide 2 mg foam once daily for 8 weeks. The co-primary endpoints were changes from baseline to Week 8 in clinical symptoms, for which clinical remission was defined as having a modified Ulcerative Colitis-Disease Activity Index [UC-DAI] subscore for stool frequency of 0 or 1 and a subscore for rectal bleeding of 0, and mucosal healing, defined as having a modified UC-DAI subscore for mucosal appearance of 0 or 1. Using a more stringent criterion, we additionally analysed deepened mucosal healing, which was defined as a mucosal appearance subscore of 0. Patient's preference, physician's global assessment, and quality of life were also assessed and analysed. Results: Overall, 286 and 291 patients were included in the 4 mg suppository and 2 mg foam groups, respectively. Budesonide 4 mg suppository met the prespecified criterion for non-inferiority to the 2 mg foam in both co-primary endpoints of clinical remission and mucosal healing. Secondary endpoints consistently supported the non-inferiority of the suppository. Trends in favour of the suppository were observed in the subgroup of mesalazine non-responders. More patients reported a preference for the suppository over rectal foam. Conclusions: In patients with ulcerative proctitis, budesonide 4 mg suppository was non-inferior to budesonide 2 mg foam in efficacy, and both were safe and well tolerated.